Las excepciones previas en el proceso contencioso administrativo (2020)
In the current regime of the prior motions at the Administrative Process and Administrative Procedure Code there are many problems and questions related to the opportunity of its formulation, processing and probatory management, so this text has the purpose to present some parameters and criteria of interpretation of this regulation, and analyze the possibility of making references to the civil procedure norms that also regulates this figure.